Fundamentals of investment management - Hirt, Goeffrey A. (McGraw-Hill, 2003)
Fundamentals of Investment Management 7/e by Hirt and Block establishes the appropriate theoretical base of investments, while at the same time applying this theory to real-world examples. The textbook provides students with a survey of the important areas of investments: valuation, the marketplace, fixed income instruments and markets, equity instruments and markets, derivative instruments, and a cross-section of special topics, such as international markets and mutual funds